2011
DOI: 10.1073/pnas.1017732108
|View full text |Cite
|
Sign up to set email alerts
|

Risk preference following adolescent alcohol use is associated with corrupted encoding of costs but not rewards by mesolimbic dopamine

Abstract: Several emerging theories of addiction have described how abused substances exploit vulnerabilities in decision-making processes. These vulnerabilities have been proposed to result from pharmacologically corrupted neural mechanisms of normal brain valuation systems. High alcohol intake in rats during adolescence has been shown to increase risk preference, leading to suboptimal performance on a decision-making task when tested in adulthood. Understanding how alcohol use corrupts decision making in this way has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 31 publications
14
96
4
Order By: Relevance
“…Daily adolescent alcohol intake was stable across the 20-day exposure period (F (19,266) day = 1.62, NS) and averaged 11.5 ± 0.98 g/kg, comparable to our previous studies ( Figure 1b; Nasrallah et al, 2011;Schindler et al, 2014). The caloric intake was comparable for alcohol-and controlexposed animals (F (6,172) day × group = 1.69, NS; F (1,29) group = 0.184, NS) and both groups increased in body weight to the same extent over the course of the 20-day exposure period (Figure 1c; F (1,35) day × group = 1.57, NS; F (1,29) group = 1.48, NS).…”
Section: Alcohol Intakesupporting
confidence: 75%
See 3 more Smart Citations
“…Daily adolescent alcohol intake was stable across the 20-day exposure period (F (19,266) day = 1.62, NS) and averaged 11.5 ± 0.98 g/kg, comparable to our previous studies ( Figure 1b; Nasrallah et al, 2011;Schindler et al, 2014). The caloric intake was comparable for alcohol-and controlexposed animals (F (6,172) day × group = 1.69, NS; F (1,29) group = 0.184, NS) and both groups increased in body weight to the same extent over the course of the 20-day exposure period (Figure 1c; F (1,35) day × group = 1.57, NS; F (1,29) group = 1.48, NS).…”
Section: Alcohol Intakesupporting
confidence: 75%
“…Importantly, a previous study in which rats were pair-housed and exposed to intragastric alcohol or control administration during adolescence observed that alcohol-treated animals showed increased lever-pressing behavior during Pavlovian conditioning consistent with the results outlined here (McClory and Spear, 2014), indicating that the effects of alcohol on learning are consistent across housing conditions. Finally, our work demonstrating that adolescent alcohol promotes maladaptive decision making (Nasrallah et al, 2011;Schindler et al, 2014), findings that we have previously linked to learning effects similar to the ones found here (Clark et al, 2012), have been replicated in animals that were group housed during intragastric alcohol administration in adolescence (Boutros et al, 2014). Thus the observed increase in sign-tracking behavior reported here is most likely the result of alcohol exposure rather than housing conditions.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In addition, the activity of midbrain dopamine neurons encodes information regarding both reward probability and delay (Fiorillo et al, 2003;Kobayashi and Schultz, 2008), suggesting that this neurochemical system processes information regarding outcome costs. Consistent with this hypothesis, a recent study found that suboptimal increases in preference for the large risky reward in the probability discounting task in a chronic ethanol exposure model were associated with a failure of mesolimbic dopamine activity to encode information about risk of reward omission (Nasrallah et al, 2011). Given that dopaminergic neurotransmission is attenuated with age (Burwell et al, 1995;Kaasinen and Rinne, 2002), it is possible that reductions in dopaminergic encoding of reward costs could account for the increased preference for the risky reward in some rats in the present study.…”
Section: Wwwfrontiersinorgsupporting
confidence: 74%